2014
DOI: 10.1371/journal.pone.0087259
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Rad51 G135C and G172T Variants and the Susceptibility to Cancer: A Meta-Analysis Involving 54 Case-Control Studies

Abstract: BackgroundThe associations between Rad51 gene polymorphisms (G135C and G172T) and risk of cancer have been investigated, but the results were inconclusive. To get a comprehensive evaluation of the association above, we performed a meta-analysis of published studies.MethodsA computerized search of PubMed, Embase and Web of Knowledge databases for all relevant studies was performed and the data were analyzed in a meta-analysis. The overall odds ratio (OR) with the 95% confidence interval (95% CI) was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
2
25
0
Order By: Relevance
“…Another RAD51 polymorphism, rs1801321 was investigated in only one meta-analysis and even though overall cancer risk was not modified [54], the decreased risk in carriers of polymorphic allele for head and neck cancer confirmed the results of previous studies [24]. Decreased breast cancer risk was also observed in carriers of polymorphic allele [58].…”
Section: Rad51supporting
confidence: 72%
See 2 more Smart Citations
“…Another RAD51 polymorphism, rs1801321 was investigated in only one meta-analysis and even though overall cancer risk was not modified [54], the decreased risk in carriers of polymorphic allele for head and neck cancer confirmed the results of previous studies [24]. Decreased breast cancer risk was also observed in carriers of polymorphic allele [58].…”
Section: Rad51supporting
confidence: 72%
“…RAD51 rs1801320 SNP was also associated with increased overall cancer risk in the two largest meta-analyses that included more than 40 individual studies [54,55], however no association was observed in an earlier study [56]. Increased risk for several cancer types, including hematological malignancies, ovarian, colorectal, and endometrial cancer was observed in a recent study [55], but not all were replicated in other studies (Table 4).…”
Section: Rad51mentioning
confidence: 93%
See 1 more Smart Citation
“…XRCC3 protein is another important protein, structurally and functionally related to RAD51, which plays an important role in the homologous recombination repair system (Krupa et al, 2011). A number of epidemiological studies have evaluated the association between RAD51 135G/C, 172 G/T and XRCC3 Thr241Met polymorphisms with pathogenesis of different cancer (Wang et al, 2013;Mao et al, 2014;Zhao et al, 2014). However, limited numbers of studies are available for above mentioned polymorphisms and HNC patients with inconclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…Both these SNPs were reported to be associated with altered gene transcription [22,23]. Large meta-analyses have shown that 135 C allele increases the general risk as well as the risk of BrC, with a distinct dosedependent effect [10,24]. The 172 T allele-containing genotypes, on the other-hand, were found to be associated with some 25% reduction of general odds of cancer compared to the 172 GG wild-type one [10].…”
Section: Introductionmentioning
confidence: 99%